ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BEI - Ma’arif, Khoirul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTOne of the reasons in choosing stock is the stock return because is regarded to be able to give more expectation value more than other investment. This research is meant to find out the influence of financial performance which is calculated by using current ratio, total assets turnover, debt to equity ratio, earning per share, and Return On Equity to the stock return at manufacturing company which is listed in Indonesia Stock Exchange. The research sample is manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2014 periods and it has been selected by using purposive sampling, so that 45 observations data have been obtained. The analysis method has been carried out by using multiple linear regressions, classic assumption test, model feasibility test with the F test and hypothesis test with the t test. The result of this research shows that Current Ratio (CR), Debt to Equity Ratio (DER and earnings per share (EPS) do not have any influence to the stock return. Meanwhile, the Return On Equity (ROE) and Total Assets Turnover (TAT) has positive influence to the stock return.Key words: current ratio, total assets turnover, debt to equity ratio, profitability, stock return.